2017
DOI: 10.1371/journal.pone.0174089
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between skin test reactivity and anti-aeroallergen IgE: Determinants among urban Brazilian children

Abstract: BackgroundThe dissociation between specific IgE and skin prick test reactivity to aeroallergens, a common finding in populations living in low and middle-income countries, has important implications for the diagnosis and treatment of allergic diseases. Few studies have investigated the determinants of this dissociation. In the present study, we explored potential factors explaining this dissociation in children living in an urban area of Northeast Brazil, focusing in particular on factors associated with poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…In the SCAALA study population, Toxocara seropositivity appeared to be a strong effect modifier of the association between anti‐aeroallergen‐IgE and that may, in part, explain the dissociation between the two markers of atopy (SPT and IgE) . Similar effect modification has been observed for infections with A. lumbricoides and T. trichiura in the same population . A possible explanation for such effect modification by helminth infections might be the presence of low‐affinity antibodies to helminths that cross‐react with arthropod allergens .…”
Section: Helminths and Allergy In Brazilsupporting
confidence: 66%
See 2 more Smart Citations
“…In the SCAALA study population, Toxocara seropositivity appeared to be a strong effect modifier of the association between anti‐aeroallergen‐IgE and that may, in part, explain the dissociation between the two markers of atopy (SPT and IgE) . Similar effect modification has been observed for infections with A. lumbricoides and T. trichiura in the same population . A possible explanation for such effect modification by helminth infections might be the presence of low‐affinity antibodies to helminths that cross‐react with arthropod allergens .…”
Section: Helminths and Allergy In Brazilsupporting
confidence: 66%
“…We also observed, in the same study population in Salvador, a marked dissociation between levels of allergen‐specific IgE and SPT to the same allergen such that many more children had detectable levels of specific IgE compared to SPT . There are several explanations for this dissociation such as competition between polyclonal and specific IgE for binding to high‐affinity receptors on mast cells and host genetic factors, among others. Additional studies are required to identify the mechanisms underlying this association …”
Section: Helminths and Allergy In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…There is conflicting data as to the influence of chronic helminth/GI nematode infection upon the incidence of allergic responses e.g. skin prick tests in humans [52]. With regards to model systems studies using chronic H .…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting data as to the influence of chronic helminth/GI nematode infection upon the incidence of allergic responses e.g. skin prick tests in humans (52). With regards to model systems studies using chronic H. polygyrus infections have shown that allergic lung responses are muted compared to non-infected animals (53, 54) and single low dose chronic infections with T. muris also influence lung allergic responsiveness (55).…”
Section: Discussionmentioning
confidence: 99%